Android Open Source Project: A study of contribution analysis & degree of openness in governance - Sharma, Harish (My University, 2021)
The term Open Source has been emerging as a popular way to collaborate & innovate. Android Open Source Project is one such, latest and widely, discussed open source project which is a Google initiative. Since its launch as an open source project, it has been one of the most widely talked about projects in technology space. While it has garnered interest from technologists and software developers across the globe, some others have started looking it through a lens of legal & business aspects. An alliance of around 80 companies was formed in the year 2007 known as Open Handset Alliance, to support and develop Android as an open and innovative mobile platform. Android has already reflected this commitment of alliance by leading the smartphone market and gaining market share at rapid pace. There are several studies conducted on Android in the recent past both as a technology platform and as its business implication. However, a little attention has been paid over the openness and governance of the platform. The objective of this thesis is to explore the openness in the governance of the Android open source project by analysis of the contributions made to the project. The contributions are studied to find key trends and their relationship with the governance. This study is unique in the way that it involves technological, legal, and business aspects in the analysis of contributions and its relationship with the governance. The study of the contribution revealed that not all the actors who are member of Open Handset Alliance are contributing to the project. Some of those who are contributing, are contributing either to push their technology or capitalize on the market strength of the Android to push products to the market. There are a lot of individuals who are also contributing to the project. The motivations behind such contributions are skill development, better job prospects etc. Some actors are not contributing to the platform directly, but they are contributing by circumventing the open contribution method. This could be due to the result of the legal implication of the contribution agreement with respect to IPRs. It was found during the study that Android Open Source Project is not governed by a group of actors by democratic means but is primarily governed by Google keeping its own interests into consideration. The project has elements of open source to the extent that the source code is available for all but when it comes to the future direction of the project is driven by only one actor, Google.
Keywords: Android, open source